EPISTEMOLOGI TAFSIR SUFI PERSPEKTIF ESOTERIK-FENOMENOLOGI - Putra, D.I Ansusa (ULUL ALBAB Jurnal Studi Islam, 2018)
This paper is a comprehensive study of sufi epistemology through interpretations of natural phenomena. The study of the triagle causality relationship between God, humans, and nature can be a binocular for studying the sufistic epistemology globally. In sufistic studies, studying natural phenomena is one way to reach the essence of God. Whereas the existence of God can be studied through His signs. This paper uses an approach from a theological scholar, Patrick Masterson, who concusively found a new approach that accommodates esoteric and exoteric dimensions simultaneously. The author considers this approach feasible to use to understand the sufistic epistemology, especially those related to natural phenomena.